(untitled) (Washington DC, 2006)
The results of the study showed that many of the standard assumptions that are used when determining the viability of sector reform programs of water, sanitation, hygiene, and poverty from coastal towns of Southwest Sri Lanka, where about 1,800 households were surveyed to gain a better understanding of the demand for piped water services by poor and non-poor households – and that tend to be rather uniformly applied across many such programs – do not always accord with consumer preferences. The study also demonstrated that different groups of consumers have different preferences and perceptions, and that insight into the various market segments that the utility is serving may be useful as it can result in a more efficient delivery of water supply services.
Keywords: Sanitation,Public health,Hygiene,Sức khỏe cộng đồng,Vệ sinh; Sri Lanka,Sri Lanka,Sri Lanka